Spectral Properties of Type Ia Supernovae and Implications for Cosmology - Nordin, Jakob (Stockholms universitet, Fysikum, 2011)
Type Ia supernovae can, for a short period of time, reach the same brightness as an entire galaxy. They are responsible for the creation of a large fraction of all heavy elements and can be used, as standard candles, to prove that the expansion of the universe is accelerating. Yet, we do not fully understand them. A basic picture where Type Ia supernovae are caused by thermonuclear explosions of white dwarfs is generally accepted, but the details are still debated. These unknowns propagate into systematic uncertainties in the estimates of cosmological parameters. A Monte Carlo framework, SMOCK, designed to model this error propagation, is presented. Evolution with time/distance and the nature of reddening are studied as the dominant astrophysical uncertainties. Optical spectra of Type Ia supernovae contain a wealth of information regarding the nature of these events, and can be used both to understand supernovae and to limit the systematic uncertainties in cosmological parameter estimates. We have reduced spectra observed with the Nordic Optical Telescope and the New Technology Telescope in conjunction with the SDSS-II supernova survey, and compared spectral properties (pseudo-Equivalent Widths and line velocities) of this sample with local supernovae.We have further studied possible systematic difficulties in such comparisons between nearby and distant supernovae, caused by noise and host galaxy contamination.Taking such uncertainties into account, we find a tentative evolution in supernova properties with redshift, compatible with expected demographic changes. Correlations with light curve shape found by other studies are confirmed. A tentative correlation with light curve colour is also presented. The latter could indicate an intrinsic component of the observed reddening, i.e. independent of interstellar dust in the host galaxy. === At the time of the doctoral defense, the following paper was unpublished and had a status as follows: Paper 4: Accepted.